UNLOCKING THE POWER OF LIQUIDITY, LEVERAGE, AND SALES GROWTH ON FINANCIAL DISTRESS: THE CRUCIAL ROLE OF PROFITABILITY AS A MODERATING FORCE - M. Alif Zaenal Fanan; Nanang Shonhadji (Center for Indonesian Accounting Studies, 2025)
Research Objective - This study examines the effect of liquidity, leverage, sales growth, and profitability as moderators of financial distress in transportation and logistics companies from 2018-2021. Method - This quantitative method analysis uses a sample of transportation and logistics companies listed on the Indonesia Stock Exchange from 2018-2021 that published annual financial reports for 2017-2020 and employs SPSS as a testing tool. Findings - A country’s economic development can be measured by its transportation and logistics industry. The research found that 14 out of 21 companies were predicted to go bankrupt between 2018-2021. Inefficient management can lead to financial distress within a company. Theoretical and Policy Implications - The implications of this research can be utilized by investors as considerations when investing in transportation and logistics companies. Research Novelty - The novelty of this study lies in the use of the Springate S-Score model for predicting financial distress, as well as addressing a research gap from previous studies.